Rancang Bangun Sistem Transmisi Mesin Peniris Minyak Bawang Goreng Tipe Spinning - Setiawan, Deny (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2024)
The spinning type fried onion oil draining machine is a tool used to drain the oil content in fried onions with a rotating work system. This machine has a transmission system to distribute power from the electric motor to the rotating tube. The transmission system used requires good and correct calculations, so that the machine can run optimally. The purpose of this study is to design and create an effective and efficient transmission system on a spinning type fried onion draining machine. The methods used include design planning, calculation of machine elements, assembly and machine testing. The results of the research showed that the required power was 0.695 kW with a rotation speed of 420 rpm, so an AC motor with a power of 1 HP and a rotation speed of 1400 rpm was chosen. The type of transmission used was a pulley and V-belt with the A-40 V-belt type with a pulley diameter on the electric motor of 75 mm and a pulley diameter on the drain shaft of 250 mm. Using a nickel chromium alloy steel transmission shaft with a diameter of 25 mm. The type of bearing used was a UCF 204 type rolling bearing with an inner diameter of 25 mm.